Putusan Hakim Agama dalam Masalah Cerai Gugat Pada Suami yang Tidak Memberi Nafkah Prespektif Hukum Positif dan Hukum Islam - Vita Firdausiyah (Program Pascasarjana Universitas Ibrahimy, 2023)
This study aims to identify the procedures for filing for divorce at the Kraksaan Religious Court, and to find out the positive legal review and Islamic law on the decision of the Religious Judge in the Divorce Lawsuit issue for husbands who do not provide a living at the Kraksaan Religious Court. The research method used is qualitative / field research (field research) where this research is descriptive. It was concluded that the procedure for carrying out a lawsuit at the Kraksaan Religious Court must meet the requirements, including a marriage book and ID card, and the religious judge's decision on divorce lawsuits for husbands who do not provide a living from the perspective of Islamic law and positive law based on existing laws and regulations. , in Islamic law that is paying attention to qoidah fiqhiyyah and also in the Qur'an surah al Baqoroh verse 229 if it is worried that the two of them cannot carry out Allah's laws, the wife is not guilty of redeeming herself to her husband so that she can be separated from her husband.